Penerapan Model Mastery Learning Dalam Pembelajaran Menulis Teks Iklan Poster Dan Slogan Pada Kelas VIII SMPN 17 Semarang - Dewi Novitasari (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This research ais to descrribe implementation of the Masteryy Learning Mode in teaching writing of advertisements, posters, and slogans in the eighth-grade class at SMPN 17 Semarang. The research method employs a qualitative descriptive approach, focusing on variables such as mastery learning, advertisements, slogans, and posters. The sample consists of one Indonesian language teacher and 30 eighth-grade students selected through purposive sampling. Data collection involves observation, Student Worksheets (LKPD), interviews, and documentation. The results indicate the effectiveness of the model's implementation, characterized by structured steps, a crucial role for the teacher, and active student involvement. Formative evaluation also aids in students' understanding and prepares them for higher levels.